Analisis Pengaruh Penggunan Uang Elektronik Terhadap Perilaku Konsumtif Mahasiswa - Dwi Rorin Mauludin Insana; Ria Susanti Johan (RELASI : JURNAL EKONOMI, 2021)
The purpose of this study was to analyze whether there was an effect of the use of electronic money on the consumptive behavior of students at the University of Indraprasta PGRI. The research method in this research is a survey method with a questionnaire. The population studied was 430 people with a sample of 81 people. Based on the research results, the sensitivity level of consumptive behavior towards the use of electronic money itself is 32% which is indicated by the regression coefficient Y = 42.26 + 0.32X. While the correlation coefficient shows r = 0.325 and the coefficient of determination (KD) of 10.56%. In the hypothesis test, the value of tcount> ttable is 3.085> 1.664. Then the hypothesis is that Ha is accepted and Ho is rejected. This means that there is a significant influence between the use of electronic money on the consumptive behavior of students of economic education at Indraprasta PGRI University. From the results above, it can be concluded that there is a positive and significant influence but has a low correlation with the contribution of using electronic money to student consumptive behavior by 10.56% and the remaining 89.44% is influenced by other factors. Keywords: non-cash payments, electronic money, consumptive behavior